2018
DOI: 10.3390/su10010197
|View full text |Cite
|
Sign up to set email alerts
|

Price Determinants of Affordable Apartments in Vietnam: Toward the Public–Private Partnerships for Sustainable Housing Development

Abstract: Abstract:Since the Doi Moi policy of economic reform in 1986, Vietnam has experienced economic development and housing market growth with increasing foreign direct investment. While high-end apartment development has dominated since the emergence of the privatized housing market, more recent focus is on the affordable apartment segment with the remarkable surge of middle-income households in Ho Chi Minh City (HCMC). While most previous studies have analyzed housing price determinants based on locational classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…On the other hand, the error term includes the spatial dependence structure and the random component. In regard to the specification of the hedonic housing price model, it is very common to use a semilog model [66][67][68][69].…”
Section: Databasementioning
confidence: 99%
“…On the other hand, the error term includes the spatial dependence structure and the random component. In regard to the specification of the hedonic housing price model, it is very common to use a semilog model [66][67][68][69].…”
Section: Databasementioning
confidence: 99%
“…Environmental externality effects are also included in this category, such as traffic noise [29][30][31][32][33], air quality [34][35][36][37], water quality [38,39], and greenspaces and parks [40][41][42][43][44]. Locational attributes indicate accessibility and proximity to major public facilities such as the central business district [45], commercial malls [46], road infrastructure [47], transportation stations [48], and schools [49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found building density, neighborhood population density, unit size, land price, pool existence, and proximity to parks, international schools, and shopping malls [50] as the fundamental determinants of housing prices. Seo et al (2018) investigated the price determinants of affordable apartments in HCMC, revealing that housing prices are significantly sensitive to proximity to downtown, access type to units, building height, foreign development, and proximity to main roads and shopping malls [46]. Huynh (2015) focused on the new town of HCMC (Phu My Hung) and found that the land size of the apartment complex, housing unit size, apartment grade, building age, building density, and proximity to dense areas significantly affect apartment prices [51].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found common factors between the two types of apartments, such as vertical shared access and proximity to downtown, as well as unique factors for each, such as more high-rise towers, foreign development, proximity to main roads, and shopping malls only for the affordable segments [16]. In order to promote the PPP, they strongly suggested regulatory reforms with revised housing laws and subsidized financial programs, because the market-friendly regulatory reform will result in a variety of beneficial effects on the housing market in developing countries such as Vietnam.…”
Section: Regulation Toward Green Technologymentioning
confidence: 99%
“…Based on the affordability framework of the housing market in Ho Chi Minh City in Vietnam, Seo et al investigated the price determinants of affordable and unaffordable apartment units using the hedonic regression model [16]. They found common factors between the two types of apartments, such as vertical shared access and proximity to downtown, as well as unique factors for each, such as more high-rise towers, foreign development, proximity to main roads, and shopping malls only for the affordable segments [16].…”
Section: Regulation Toward Green Technologymentioning
confidence: 99%